Question

x^3y''' - x^2y'' - 3xy' =3x

x^3y''' - x^2y'' - 3xy' =3x

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
x^2y''-3xy'+3y=x^-2
x^2y''-3xy'+3y=x^-2
x^3y’’’+3x^2y”+2xy’=0
x^3y’’’+3x^2y”+2xy’=0
Solve the following nonhomogenous Cauchy-Euler equations for x > 0. a. x^(2)y′′+3xy′−3y=3x^(2).
Solve the following nonhomogenous Cauchy-Euler equations for x > 0. a. x^(2)y′′+3xy′−3y=3x^(2).
Show that the function f(z) =x^3-3xy^2+i((3x^2y-y^3) is differentiable
Show that the function f(z) =x^3-3xy^2+i((3x^2y-y^3) is differentiable
Solve for the general solution x^4y''''+4x^3y'''+3x^2y''-xy'+y=0
Solve for the general solution x^4y''''+4x^3y'''+3x^2y''-xy'+y=0
use gauss Jordan to solve 5x+11y+5z=42 x+2y+2z=9 3x+3y+2z=35
use gauss Jordan to solve 5x+11y+5z=42 x+2y+2z=9 3x+3y+2z=35
Verify that the given function is the solution of the initial value problem. 1. A) x^3y'''-3x^2y''+6xy'-6y=...
Verify that the given function is the solution of the initial value problem. 1. A) x^3y'''-3x^2y''+6xy'-6y= -(24/x) y(-1)=0 y'(-1)=0 y''(-1)=0 y=-6x-8x^2-3x^3+(1/x) C) xy'''-y''-xy'+y^2= x^2 y(1)=2 y'(1)=5 y''(1)=-1 y=-x^2-2+2e^(x-1-e^-(x-1))+4x
5. The planes: 2x − 3y + z = 1 and 3x − 2y − z...
5. The planes: 2x − 3y + z = 1 and 3x − 2y − z = 0 … (Explain/Show your Work) a. Are parallel b. Are Coincident c. Meet in a Line d. Meet at a Point
Consider the following system of equations. 3x − 2y = b1 4x + 3y = b2...
Consider the following system of equations. 3x − 2y = b1 4x + 3y = b2 (a) Write the system of equations as a matrix equation. x y = b1 b2 (b) Solve the system of equations by using the inverse of the coefficient matrix.(i) where b1 = −6, b2 = 11 (x, y) =       (ii) where b1 = 4, b2 = −2 (x, y) =      
Use Gaussian Elimination to solve and show all steps: 1. (x+4y=6) (1/2x+1/3y=1/2) 2. (x-2y+3z=7) (-3x+y+2z=-5) (2x+2y+z=3)
Use Gaussian Elimination to solve and show all steps: 1. (x+4y=6) (1/2x+1/3y=1/2) 2. (x-2y+3z=7) (-3x+y+2z=-5) (2x+2y+z=3)
ADVERTISEMENT
Need Online Homework Help?

Get Answers For Free
Most questions answered within 1 hours.

Ask a Question
ADVERTISEMENT